New insights into the heat responses of grape leaves via combined phosphoproteomic and acetylproteomic analyses. Issue 1 (1st September 2019) - Liu, Guo-Tian; Jiang, Jian-Fu; Liu, Xin-Na; Jiang, Jin-Zhu; Sun, Lei; Duan, Wei; Li, Rui-Min; Wang, Yi; Lecourieux, David; Liu, Chong-Huai; Li, Shao-Hua; Wang, Li-Jun
Abstract: Heat stress is a serious and widespread threat to the quality and yield of many crop species, including grape ( Vitis vinifera L.), which is cultivated worldwide. Here, we conducted phosphoproteomic and acetylproteomic analyses of leaves of grape plants cultivated under four distinct temperature regimes. The phosphorylation or acetylation of a total of 1011 phosphoproteins with 1828 phosphosites and 96 acetyl proteins with 148 acetyl sites changed when plants were grown at 35 °C, 40 °C, and 45 °C in comparison with the proteome profiles of plants grown at 25 °C. The greatest number of changes was observed at the relatively high temperatures. Functional classification and enrichment analysis indicated that phosphorylation, rather than acetylation, of serine/arginine-rich splicing factors was involved in the response to high temperatures. This finding is congruent with previous observations by which alternative splicing events occurred more frequently in grapevine under high temperature. Changes in acetylation patterns were more common than changes in phosphorylation patterns in photosynthesis-related proteins at high temperatures, while heat-shock proteins were associated more with modifications involving phosphorylation than with those involving acetylation. Nineteen proteins were identified with changes associated with both phosphorylation and acetylation, which is consistent with crosstalk between these posttranslational modification types.